A Focused Review of Language Use Preceding Death by Execution - Hirschmüller, Sarah; Egloff, Boris (Frontiers in Psychology, 2018)
Executions are one form of death that can be assumed to be maximally anxiety provoking. Words spoken by death row inmates moments before their execution can provide valuable insights into people’s end-of-life communication needs and themes, conveying what individuals choose to express to others in the face of imminent death. In this focused review, we describe findings from quantitative and qualitative text analysis studies that have analyzed affective experiences and meaning-making attempts in transcriptions of actual statements made by Texas death row inmates. Overall, the most prevalent content themes identified in these final acts of verbal communication in the reviewed studies consisted of a strong predominance of emotional positivity, messages to relevant social others, and spiritual references. We subsequently view the reviewed findings in the light of additional research in which people’s conceptions of death and dying were explored and language studies in which people’s communication before other forms of death was analyzed. Finally, we describe open questions and directions for future analyses of death row inmates’ final statements, and we outline practical implications.